IMPACT OF ORGANIZATIONAL LEARNING ON JOB SATISFACTION, COMMITMENT, AND PERFORMANCE OF PRIVATE BANK EMPLOYEES - Turangan, Joyce A.; Ruslim, Herman (International Journal of Application on Economics and Business, 2025)
Employee performance serves as a vital measure in projecting future success within organizations. Key factors that influence this performance include organizational learning, job satisfaction, and employee commitment. This research investigates how organizational learning affects job satisfaction, organizational commitment, and employee performance, alongside the impact of job satisfaction and organizational commitment on performance outcomes. A quantitative method was applied through non-probability sampling, specifically convenience sampling. Primary data were obtained via an online survey involving 105 private bank employees in Tangerang, and analyzed using SmartPLS 4. The findings reveal that all proposed variables significantly and positively influence employee performance. Moreover, both job satisfaction and organizational commitment are proven to partially mediate the relationship between organizational learning and employee performance.